Linguistic landscape of a multilingual city: regional specificity (by the material of the Italian city of Aosta) - Panteleenko, Alessia A. (Journal of the Belarusian State University. Philology, 2023)
The study determines the functional potential of the Italian, French and Franco-Provençal languages in the communicative space of the city of Aosta. Significant differences in the use of languages in the written texts of the urban environment are revealed: French language dominates in the formation of the text of street signs; Italian and French languages are quite active in the names of commercial establishments; the names of state institutions are always bilingual; French and Italian languages texts appear on posters; only Italian language is used in obituaries, in other groups there is no definite trend, Italian or French language, or a combination of both can be used. A comparative analysis of the texts of the linguistic landscape and the speech preferences of the population made it possible to establish the specifics of the functioning of languages in the written and oral spheres of communication. Unlike intracity texts, where Italian and French languages are actively used, Italian and Franco-Provençal languages have the greatest demographic power in the speech of residents, which determines the regional specifics of the linguistic landscape of the Italian city of Aosta.
Keywords: French language; Italian language; Franco-Provençal language; urban nominations; language demographic power